Exploring the Role of Geography and History in Environmental Education: Shaping Teacher Training in Human Sciences Contexts - Freitas, Mirlaine Rotoly de (Revista Brasileira de Educação Ambiental (RevBEA), 2025)
This work proposes adjustments to the Pedagogy curriculum and Geography and History programs to strengthen environmental education in elementary schools. Pedagogy plays a crucial role in teacher training and integrating environmental content. Enhancing these curricula and including environmental themes in Geography and History foster an interdisciplinary approach, essential for addressing environmental challenges and providing effective education.